Why do democracies respond differently to COVID-19? A comparison of the United States and South Korea - Yexin Mao (Frontiers in Public Health, 2024)
BackgroundCOVID-19 has posed severe challenges to crisis management in democracies. Different democracies respond to the crisis differently. This article proposes an analytical framework to explain why democracies respond differently to the public health crisis and how different contextual factors affect crisis response in democracies.MethodsBy comparing COVID-19 responses in the US and South Korea, this article conducts a comparative case study with a most similar system design. The two countries have been selected as cases because they are both developed democracies with a robust healthcare system. However, different contextual factors in the two countries have created different crisis responses by shaping different crisis leadership and political and social solidarity. This study collected data from different sources, including government documents, official websites, leaders’ speeches, research reports, academic articles and news media. We tried to enhance the reliability of the data by comparing different data sources.ResultsWe found that individual, institutional and cultural dimensions of contextual factors can influence different crisis responses of democratic countries by shaping crisis leadership and political and social solidarity. On the individual and institutional dimensions, leadership style and governance structure shape crisis leadership (sense making, decision making and coordinating, and meaning making), which in turn influences crisis management. On the cultural dimension, political and social solidarity measured by political polarization and social cooperation are shaped by cultural and social norms.ConclusionOur findings indicate that democracies require strong crisis leadership and a high degree of political and social solidarity to tackle public health crises. A centralized and coordinated system, as well as a political elite leadership style shaped by rich crisis response experience, expertise and high sensitivity to crises are conducive to crisis management. Fostering a cultural and social norm that facilitates state–society collaboration can promote crisis management. These findings provide valuable insights for decision-makers to effectively respond to future pandemics.